88.3k views
0 votes
Solve by completing the square:
x^2 + 3x - 9 = 0

User Ben Lee
by
4.6k points

2 Answers

2 votes

Answer:

2 solutions. x = -3/2 + 3/2 * sqrt(5) and x = -3/2 + -3/2 * sqrt(5)

Explanation:

Let's solve your equation step by step.

x^2 + 3x −9 = 0

For this equation: a=1, b=3, c=-9

1x^2 + 3x+ −9 = 0

Step 1: Use quadratic formula with a=1, b=3, c=-9.

x = (-b ±
√(b^2 - 4ac))/2a

x = (-3 ±
√(3^2 - 4(1)(-9)))/2a

x = (-3 ±
√(45))/2

x = -3/2 + 3/2 * sqrt(5) or x = -3/2 + -3/2 * sqrt(5)

User Majid Savalanpour
by
5.1k points
3 votes

Answer:

Explanation:

x^2 + 3x - 9 =0

By comparing with the equation ax^2+bx+c = 0,

we get,

a = 1, b=3, c = -9

we know the formula for x is,

x = (-b±√(b^2 - 4ac))/2a

x = (-3±√45)/2

x = (-3±3√5)/2

x = (-3+3√5)/2, (-3-3√5)/2

User Werewolve
by
4.4k points